Extended-spectrum antibiotics for community-acquired pneumonia with a low risk for drug-resistant pathogens. (November 2022) - Kobayashi, Hironori; Shindo, Yuichiro; Kobayashi, Daisuke; Sakakibara, Toshihiro; Murakami, Yasushi; Yagi, Mitsuaki; Matsuura, Akinobu; Sato, Kenta; Matsui, Kota; Emoto, Ryo; Yagi, Tetsuya; Saka, Hideo; et al.
Highlights: This study focused on the use of extended-spectrum antibiotics in patients with community-acquired pneumonia with a low risk for drug-resistant pathogens (DRPs). Unnecessary extended-spectrum antibiotics use was defined by the 2019 community-acquired pneumonia guidelines. Extended-spectrum antibiotics use was associated with increased 30-day mortality. Risk assessment of DRPs is essential in determining empirical antibiotic therapy. Extended-spectrum antibiotics use may be harmful in patients with a low risk for DRPs. Abstract: Objectives: The potential hazards of extended-spectrum antibiotic therapy for patients with community-acquired pneumonia (CAP) with low risk for drug-resistant pathogens (DRPs) remain unclear; however, risk assessment for DRPs is essential to determine the initial antibiotics to be administered. The study objective was to assess the effect of unnecessary extended-spectrum therapy on the mortality of such patients. Methods: A post hoc analysis was conducted after a prospective multicenter observational study for CAP. Multivariable logistic regression analysis was performed to assess the effect of extended-spectrum therapy on 30-day mortality. Three sensitivity analyses, including propensity score analysis to confirm the robustness of findings, were also performed. Results: Among 750 patients with CAP, 416 with CAP with a low risk for DRPs were analyzed; of these, 257 underwent standard therapy and 159 underwent extended-spectrum therapy. The 30-day mortality was 3.9% and 13.8% in the standard and extended-spectrum therapy groups, respectively. Primary analysis revealed that extended-spectrum therapy was associated with increased 30-day mortality compared with standard therapy (adjusted odds ratio 2.82; 95% confidence interval 1.20-6.66). The results of the sensitivity analyses were consistent with those of the primary analysis. Conclusion: Physicians should assess the risk for DRPs when determining the empirical antibiotic therapy and should refrain from administering unnecessary extended-spectrum antibiotics for patients with CAP with a low risk for DRPs.